2019
DOI: 10.1093/biolre/ioz054
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases 2 and 9 are elevated in human preterm laboring uterine myometrium and exacerbate uterine contractility†

Abstract: Matrix metalloproteinases 2 and 9 (MMP2/9) have previously been shown to be elevated in serum and amniotic fluid from women undergoing preterm birth. We performed experiments to determine the effects of MMP2/9 on uterine contraction and birth timing. Pregnant mice were injected daily with 50 mg/kg of SB-3CT or vehicle control beginning on gestational day 14-18 to determine if MMP2/9 inhibition would affect parturition timing. MMP2/9 expression in human myometrial tissue was determined by Simple Western (Wes) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…MMP-9 is known to be expressed by many cells at the maternal foetal interface including: neutrophils; macrophages; NK cells; vascular endothelial cells of the decidua; cervical fibroblasts and epithelial cells ( Lockwood et al., 2008 ; Naruse et al., 2009 ; Gonzalez et al., 2011 ; Ulrich et al., 2019 ). Gonzalez and colleagues demonstrated that in PTB macrophages are the main source of MMP-9 at the cervix, whereas MMP-9 production at term is non-leucocyte dependant ( Gonzalez et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-9 is known to be expressed by many cells at the maternal foetal interface including: neutrophils; macrophages; NK cells; vascular endothelial cells of the decidua; cervical fibroblasts and epithelial cells ( Lockwood et al., 2008 ; Naruse et al., 2009 ; Gonzalez et al., 2011 ; Ulrich et al., 2019 ). Gonzalez and colleagues demonstrated that in PTB macrophages are the main source of MMP-9 at the cervix, whereas MMP-9 production at term is non-leucocyte dependant ( Gonzalez et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 (also known as gelatinase B) is a zinc dependent endopeptidase involved in extracellular matrix (ECM) remodelling of type IV collagen (and to lesser extent type V) and elastin that is part of several physiological processes including uteroplacental re-modelling in reproduction, cell migration (particularly neutrophils), angiogenesis and wound healing(Juanjuan Chen and Khalil, 2017 ). It is known to be upregulated in membrane rupture, placental detachment and myometrial contractility in term and preterm labour ( Weiss et al., 2007 ; Sundrani et al., 2012 ; Ulrich et al., 2019 ). MMP-9 expression occurs in multiple cell types, many of which are found at the maternal-foetal interface although the source of MMP-9 in the events leading to labour is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that TNF- α has a certain correlation with the contractility of the myometrium, mainly by affecting the expression of progesterone (PG) and Matrix Metallopeptidase 9 (MMP9). The increase in the expression and sensitivity of PG and MMP9 in the myometrium will lead to uterine contraction and delivery (Refs 47 , 48 ). Specifically, TNF- α has been reported to reduce the activity and expression of NAD+-dependent 15-hydroxyprostaglandin dehydrogenase (PGDH) in trophoblast cells, resulting in maternal PE and premature delivery (Ref.…”
Section: Tnf- α In Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…Towards the end of pregnancy and in labour, the uterus goes through a set of gradual biochemical, anatomical, endocrine and immune changes that transform it from a quiescent state maintaining pregnancy, to the activated contractile state, ready for labour (4)(5)(6). Key transformations within reproductive tissues include cervical remodelling and dilatation, fetal and decidual membrane activation and an increase in myometrial contractility (5, [7][8][9]. An increase in myometrial contractility results from changes in expression of proteins that promote intercellular connectivity and excitability of myocytes (6,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%